Educational attainment of children born to mothers with epilepsy. Issue 7 (27th March 2018) - Lacey, Arron S; Pickrell, William Owen; Thomas, Rhys H; Kerr, Mike P; White, Cathy P; Rees, Mark I
Abstract : Objective: Small prospective studies have identified that children exposed to valproate in utero have poorer scores on cognitive testing. We wanted to identify whether children exposed to antiepileptic drugs (AEDs) in utero have poorer school performance. Methods: We used anonymised, linked, routinely collected healthcare records to identify children born to mothers with epilepsy. We linked these children to their national attainment Key Stage 1 (KS1) tests in mathematics, language and science at the age of 7 and compared them with matched children born to mothers without epilepsy, and with the national KS1 results. We used the core subject indicator (CSI) as an outcome measure (the proportion of children achieving a minimum standard in all subjects) and the results in individual subjects. Results: We identified 440 children born to mothers with epilepsy with available KS1 results. Compared with a matched control group, fewer children with mothers being prescribed sodium valproate during pregnancy achieved the national minimum standard in CSI (−12.7% less than the control group), mathematics (−12.1%), language (−10.4%) and in science (−12.2%). Even fewer children with mothers being prescribed multiple AEDs during pregnancy achieved a national minimum standard: CSI (by −20.7% less than the control group), mathematics (−21.9%), language (−19.3%) and science (−19.4%). We did not observe any significant difference in children whose mothers were prescribed carbamazepine or were not taking an AED when compared with the control group. Conclusions: In utero exposure to AEDs in combination, or sodium valproate alone, is associated with a significant decrease in attainment in national educational tests for 7-year-old children compared with both a matched control group and the all-Wales national average. These results give further support to the cognitive and developmental effects of in utero exposure to sodium valproate as well as multiple AEDs, which should be balanced against the need for effective seizure control for women during pregnancy.